Cholesterol‐lowering activity of natural mono‐ and sesquiterpenoid compounds in essential oils: A review and investigation of mechanisms using in silico protein–ligand docking. (22nd March 2021) - Bahr, Tyler; Butler, Gavin; Rock, Christian; Welburn, Kyle; Allred, Kathryn; Rodriguez, Damian
Abstract : Mono‐ and sesquiterpenoids are the main chemical constituents of essential oils. Essential oils and their constituents have received increasing attention for lipid‐lowering properties in both cell and animal models. Despite the chemical diversity of essential oil compounds, the effects of many of these compounds on cholesterol metabolism are highly similar. In this report, we review the literature regarding the effects of essential oils and their terpenoid constituents on cholesterol homeostasis, and explore likely mechanisms using protein–ligand docking. We identified 98 experimental and seven clinical studies on essential oils, isolated compounds, and blends; 100 of these described improvements either in blood cholesterol levels or in sterol metabolic pathways. Our review and docking analysis confirmed two likely mechanisms common to many essential oil compounds: (1) direct agonism of peroxisome‐proliferator‐activated receptors, and (2) direct interaction with sterol‐sensing domains, motifs found in key sterol regulatory proteins including sterol regulatory element binding protein cleavage activating protein and HMG‐CoA reductase. Notably, these direct interactions lead to decreased transcription and accelerated degradation of HMG‐CoA reductase. Our work suggests that terpene derivatives in essential oils have cholesterol‐lowering activity and could potentially work synergistically with statins, however, further high quality studies are needed to establish their clinical efficacy.